Effects of river damming in Neotropical piscivorous and omnivorous fish: feeding, body condition and abundances - Pereira,Larissa Strictar (2016)
ABSTRACT The increase in abundance of small-sized fishes is common after a reservoir is formed. There is an increase in the consumption of fish, from typically piscivorous fish to opportunistic species that take advantage of abundant resources. This study aims to evaluate the effects of diet changes induced by damming on the feeding activity and condition factor of typically piscivorous (Hoplias aff. malabaricus and Oligosarcus longirostris ) and opportunistic (Astyanax lacustris (ex Astyanax altiparanae ) and Pimelodus britskii ). Sampling was conducted before and after the impoundment in the Iguaçu River in the region of Salto Caxias, Paraná State, Brazil. Stomach contents were analysed by the volumetric method. Feeding activity and body condition were inferred by the mean stomach repletion index and the mean condition factor. Typically piscivorous species presented a general tendency of decreased feeding activity and increased condition factor, while opportunistic species, presented a decrease in condition and feeding activity in the most affected sites. The increase in the condition factor of piscivorous fish suggests that these species benefit by the increased abundance of small size prey fish. Some opportunist species that do not have adjustments for the piscivorous diet, regardless of the intensity of consumption and resource availability, can suffer negative reflex when adopting a piscivorous diet.